Different gut microbiome composition in obese Guizhou minipigs between female and castrated male - Yao, Gang; Wu, Shuguang; Zeng, Xianchun; Zhao, Hai; Wang, Guoqi; Chen, Mingfei; Qian, Ning (Folia microbiologica, 2019)
Gut microbiome lives in the intestinal tract of animals and plays an important role in almost all life processes. Gut microbiome balance is beneficial to health, and imbalance leads to many diseases, one of which is obesity epidemic. However, gut microbiome is also influenced by host hormone, and different gut microbiome composition is observed between the sexes. Here, we studied whether castrated male Guizhou minipigs with obesity own the same gut microbiome composition and microbial function predictions with those in obese females. We sequenced the hypervariable regions V3 to V4 of bacterial 16s rRNA of fecal samples collected from our study subjects. We observed that the operational taxonomic units were small, which suggested that the abundance of gut microbiome may be influenced by low genetic diversity of host. Our results also suggested that the castrated male has different gut microbial composition compared to the obese female. An increasing Firmicutes/Bacteroidetes ratio was observed in both castrated male and obese female groups, which suggested that the main adipogenic gut microorganism in obese Guizhou minipigs in our studies is the same with that in other obese mammals. However, we also observed that there were function prediction differences of obese Guizhou minipigs between female and castrated male, which suggested that the influence of gut microbiome on obesity between them is different.
Keywords: prasata; Feces; Swine; modely nemocí na zvířatech; Male; Obesity; fylogeneze; Castration; RNA, Ribosomal, 16S; Sequence Analysis, DNA; Phylogeny; sekvenční analýza DNA; Bacteria; obezita; Gastrointestinal Microbiome; mužské pohlaví; Swine, Miniature; kastrace; střevní mikroflóra; DNA, Bacterial; DNA bakterií; Animals; ženské pohlaví; zvířata; Disease Models, Animal; RNA ribozomální 16S; Female; feces; miniaturní prasata